Prevalence of Mood and Anxiety Disorders Among Adults Seeking Care in Primary Healthcare Centers in Cordoba, Argentina. - Burrone, María Soledad; Alvarado, Rubén; Colantonio, Lisandro D.; Enders, Julio E.; Abeldaño Zuñiga, Roberto Ariel; Valencia, Eliecer; Susser, Ezra; Fernández, Ruth A. (Frontiers in Psychiatry, 2020)
Objective To estimate the prevalence of mood and anxiety disorders among adults seeking care in primary healthcare centers in Cordoba city, Argentina. Methods Cross-sectional analysis of a random sample of adults 18–69 years of age seeking care for general health problems in public (i.e., government-funded) primary healthcare centers in Cordoba city, Argentina in 2010–2011. Mood and anxiety disorders were assessed in the participants’ lifetime, and in the last 12 months and 30 days using the World Mental Health Composite International Diagnostic Interview 3.0, and defined following the International Classification of Diseases, tenth revision. Results Overall, 1,067 participants were included in the current analysis [mean age 35.6 (SD 13.2) years, 83.7% female]. The lifetime, 12-month and 30-day prevalence of any mood or anxiety disorder was 40.4% [95% confidence interval (95%CI) 37.4–43.4%], 20.1% (17.8–22.7%) and 7.8% (6.2–9.6%), respectively. The prevalence of anxiety disorders was higher compared to mood disorders when assessed in the participants’ lifetime [29.7% (95%CI 27.0–32.5%) versus 19.3% (17.0–21.8%)], and in the last 12 months [14.9% (12.8–17.2%) versus 8.7% (7.1–10.6%)] and 30 days [5.8% (4.5–7.4%) versus 2.3% (1.5–3.4%)]. Age and marital status-adjusted odds ratios for any mood or anxiety disorder in the participants’ lifetime and in the last 12 months and 30 days comparing women versus men were 1.19 (95%CI 0.85–1.67), 1.70 (1.07–2.69), and 2.26 (1.02–5.00), respectively. Conclusion The prevalence of mood and anxiety disorders is high among adults seeking care in primary healthcare centers in Cordoba city, particularly among women. Integration of primary and mental health services is warranted.